2015
DOI: 10.1037/xlm0000036
|View full text |Cite
|
Sign up to set email alerts
|

The influence of reference acceptance and reuse on conversational memory traces.

Abstract: Not all pieces of information mentioned during an interaction are equally accessible in speakers’ conversational memory. The current study sought to test whether 2 basic features of dialogue management (reference acceptance and reuse) affect reference recognition. Dyads of speakers were asked to discuss a route for an imaginary person, thus referring to the landmarks to be encountered. The results revealed that the participants’ conversational memory for the references produced during the interaction depended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
4
12
0
Order By: Relevance
“…The results corroborated this idea, as the participants recalled the content words they had generated themselves better than the content words which had been generated by their partner. This confirms and extends previous work on how production and generation affect collaborative dialogue (Knutsen & Le Bigot, 2014;Knutsen et al, in press), shedding light on how lowlevel processes affect speakers' memory for past interactions (see also Knutsen & Le Bigot, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The results corroborated this idea, as the participants recalled the content words they had generated themselves better than the content words which had been generated by their partner. This confirms and extends previous work on how production and generation affect collaborative dialogue (Knutsen & Le Bigot, 2014;Knutsen et al, in press), shedding light on how lowlevel processes affect speakers' memory for past interactions (see also Knutsen & Le Bigot, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…To answer this question, the current study examined participants' recognition of references to landmarks presented and accepted during an interaction with a simulated dialogue system. First, the results confirmed that the participants remembered the references they had presented themselves better than the references that had been presented by the system, confirming that the self-presentation bias also occurs in human-system dialogue (Knutsen & Le Bigot, 2015;Knutsen et al, in press). This is also in line with the idea that similar psychological processes are at play when human beings interact with other humans or with automated dialogue systems (Brennan, 1991;Powers et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…When two human partners interact, they remember better self-presented information and/or information accepted through verbatim repetition (Knutsen & Le Bigot, 2015;Knutsen et al, in press). Is this also the case when a human user interacts with a system?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations